Generalized Logarithmic Penalty Function Approach For Invex Nonlinear Constrained Optimization And Its Application - Hassan, Mansur (2020)
A penalty function approach is used widely in the field of mathematical programming, and it served as an alternative to conventional non-linear constrained optimization approach. In a quest to make an advancement theoretically and progress practically, we proposed a continuously differentiable penalty function to handle the nonlinear constrained optimization problem; it is called logarithmic penalty function (LPF) method.